First Report Of Phomopsis Canker Caused By Phomopsis Mali From India (Applied Biological Research, 2011)
During disease survey in apple orchards in Kashmir valley in 2009-2010, the apple twigs were noticed to be affected by canker disease. These cankers were observed to be incited by Phomopsis mali Robert and the  pathogen is a new record from India.
Keywords: Apple; canker; India; Phomopsis mali